Bright air, brilliant fire : on the matter of the mind - Edelman, Gerald M.; Rogers D. Spotswood Collection (London : Penguin Books, 1992)
We are on the brink of understanding ancient mysteries: how we know, what governs our nature, what makes a person different from a thing. In the last decade, more than twenty disciplines dealing with every aspect of the brain have contributed to a revolution in the neurosciences--a revolution as significant, in the view of many observers, as the Galilean and Copernican revolutions in mathematics and physics or the Darwinian revolution in biology. In this book, one of the world's foremost brain scientists gives us a glimpse into the workings of the human brain--the most complex material object in the universe. A match head's worth of the brain contains about a billion connections that can combine in ways which can only be described as hyperastronomical--on the order of ten followed by millions of zeros (there are only about ten followed by eighty zeros' worth of positively charged particles in the whole known universe). Gerald Edelman takes us on a dazzling tour through such diverse topics as Turing machines, Darwin's'program,' Jamesian flights and perchings, genetics, quantum physics, and the nature of perception, language, and individuality. He argues that biology will provide the key to understanding the brain and ultimately the mind. Underlying this argument is the evolutionary view that the mind arose at a definite time in history. This sweeping book considers our place in nature and how we came to be able to describe and change it. It examines the implications of understanding the brain for philosophy, for curing mental disease, and for the possibility of building conscious artifacts. Edelman does not hesitate to take on cognitive and behavioral approaches that leave biology out of the picture, as well as the currently fashionable view of the brain as a computer. He argues that the workings of the brain more closely resemble the living ecology of a jungle than they do the activities of an electric company. Some startling conclusions emerge from these ideas: individuality is necessarily at the very center of what it means to have a mind; no creature is born value-free; no physical theory of the universe can claim to be a'theory of everything' without including an account of how the brain gives rise to the mind. There is no greater scientific challenge than understanding the brain. Here's the book that provides a window on that understanding.
pt. I: Problems. 1: Mind. 2: Putting the Mind Back into Nature. 3: The Matter of the Mind -- pt. II: Origins. 4: Putting Psychology on a Biological Basis. 5: Morphology and Mind: Completing Darwin's Program. 6: Topobiology: Lessons from the Embryo. 7: The Problems Reconsidered -- pt. III: Proposals. 8: The Sciences of Recognition. 9: Neural Darwinism. 10: Memory and Concepts: Building a Bridge to Consciousness. 11: Consciousness: The Remembered Present. 12: Language and Higher-Order Consciousness. 13: Attention and the Unconscious. 14: Layers and Loops: A Summary -- pt. IV: Harmonies. 15: A Graveyard of Isms: Philosophy and Its Claims. 16: Memory and the Individual Soul: Against Silly Reductionism. 17: Higher Products: Thoughts, Judgments, Emotions. 18: Diseases of the Mind: The Reintegrated Self. 19: Is It Possible to Construct a Conscious Artifact? 20: Symmetry and Memory: On the Ultimate Origins of Mind -- Mind Without Biology: A Critical Postscript.
Includes bibliographical references : (pages 253-266) and index.
Keywords: Mind and body; Neuropsychology; Philosophy of mind; Neuropsychology; Philosophy